2019
DOI: 10.1093/annweh/wxz067
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Job-Exposure Matrix for Assessment of Occupational Exposure to High-Frequency Electromagnetic Fields (3 kHz–300 GHz)

Abstract: Objectives The aim of this work was to build a job-exposure matrix (JEM) using an international coding system and covering the non-thermal intermediate frequency (IF) (3–100 kHz, named IFELF), thermal IF (100 kHz–10 MHz, named IFRF), and radiofrequency (RF) (>10 MHz) bands. Methods Detailed occupational data were collected in a large population-based case–control study, INTEROCC, with occupations coded into the Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Finally, considering high frequency fields, more precise data are available; recently, in a large multicenter study involving almost 10,000 subjects and over 35,000 different occupations, a job exposure matrix (JEM) was applied, retrieving exposure data for 468 different occupational groups. The results showed that the 62% of the occupations were exposed to high frequency EMF [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, considering high frequency fields, more precise data are available; recently, in a large multicenter study involving almost 10,000 subjects and over 35,000 different occupations, a job exposure matrix (JEM) was applied, retrieving exposure data for 468 different occupational groups. The results showed that the 62% of the occupations were exposed to high frequency EMF [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we believe that a comprehensive summary on what is known on the medical aspects related to the prevention of occupational EMF exposure risk, according to the definition of the risk provided in the current legislation in Europe, can give an important contribution to the advancement of the research. The possible health risk should be considered not only in relation to the specific scenarios of excessive exposure but also during standard exposure conditions, such those usually reported for the majority of the occupational groups [ 1 , 3 , 4 ]. Among the main questions that have to be answered by researchers in this field there are: (i) the identification of the workers at risk for adverse effects induced by the occupational EMF exposure; (ii) the possible EMF-related effects to be investigated by the physicians of the exposed subjects, according to the type of EMF; and (iii) the types of medical practices that physicians can follow for the monitoring of the health status of EMF-exposed workers, for the detection of eventual effects associated to the EMF, and for an appropriate medical prevention.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, one of the first suggestions regards an exposure categorization for the different professions working with MRI equipment, that could be based, for example, on the nature of the fields they are exposed to, the time that they are exposed, and the procedures that they perform. Some tools generally used to assess exposure to potential health hazards in occupational epidemiological studies, such as the job-exposure matrix, could aid [9,168,169].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies improved on exposure characterization by using expert assessment and job- or source-exposure matrices (JEM, SEM). Existing JEMs of occupational RF exposure ( Karipidis et al, 2008 , Kauppinen et al, 1998 , Migault et al, 2019 , Siemiatycki and Lavoué, 2018 ), provide exposure estimates often based on a small number of measurements per source and/or job, and may not be informative about the probability of exposure per occupation, the typical exposure of workers in specific jobs, and the variability of exposure levels by task, working practices, and over time. These drawbacks also apply to the most recent RF-JEM ( Migault et al 2019 ), comprising 282 occupational titles, and built by combining source-based measurements from the literature ( Vila et al 2016 ) with occupational data collected in the INTEROCC case-control study (≈ 9,300 participants from seven countries).…”
Section: Methodsmentioning
confidence: 99%
“…It might also result in excluding potentially informative longitudinal studies of occupational groups with high probability and/or intensity of RF-exposure, and limited co-exposures to established carcinogens. To identify occupations meeting these requirements, we selected the activities with a yearly cumulative exposure ≥ 250 W/m 2 hour from the Israeli measurement survey ( Hareuveny et al 2015 ), and the job titles with an exposure probability > 20% from the INTEROCC JEM ( Migault et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%